Unique characteristics of end-of-life hospitalizations in Parkinson disease - Aamodt, Whitley W.; Dahodwala, Nabila; Bilker, Warren B.; Farrar, John T.; Willis, Allison W. (Frontiers in Aging Neuroscience, 2023)
Introduction: Little is known about inpatient outcomes across the Parkinson disease (PD) trajectory, or whether hospitalizations occurring in the last 6 months of life differ from earlier hospitalizations. Methods: This cross-sectional study compared Medicare beneficiaries aged 65 and older with PD: decedents who died between 7/1/2017-12/31/2017 from all causes and were hospitalized at least once in their last 6 months of life, and non-decedents who were hospitalized between 1/1/2017-6/30/2017 and lived 6 or more months after discharge. Patient-level variables (demographics, comorbidities, treatment intensity) and encounter-level variables (length of stay, total charges) were compared between groups. Multivariable logistic regression models compared rates of intensive care unit (ICU) admission and 30-day readmission, adjusting for age, sex, race/ethnicity, rural residence, and Charlson Comorbidity Index. Results: Of 26,492 Medicare decedents with PD, 16,187 (61.1%) were hospitalized in their last 6 months of life. Of 347,512 non-decedents with PD, 62,851 (18.1%) were hospitalized in a 6-month period. Hospitalized decedents were older than hospitalized non-decedents and had more comorbidities. Compared to earlier hospitalizations, end-of-life hospitalizations were longer (5 [IQR 3-9] vs. 4 [IQR 3-7] days) and more expensive (36,323 [IQR 20,091-69,048] vs. 32,309 [IQR 18,789-57,756]). In regression models, hospitalized decedents had greater odds of ICU admission (AOR 2.36; CI 2.28-2.45) and 30-day readmission (AOR 2.43; CI 2.34-2.54). Discussion: Hospitalizations occurring in the end-of-life period are longer, more costly, and more resource intensive than earlier hospitalizations. Once hospitalized, ICU admission and 30-day readmission may aid in prognostication and serve as markers of transition to the end-of-life period.